Analisis Persepsi Mahasiswa Pendidikan Bahasa Jepang Universitas Negeri Semarang Terhadap Aksen Bahasa Jepang - Iqkhoh Lusiana; Heni Hernawati (Undiksha Press, 2024)
This study aims to determine the ability of Japanese Language Education students at Semarang State University in identifying Japanese accents. The research method used is descriptive qualitative with data sources taken from the results of respondents' answers to perception tests regarding Japanese accents. The perception test was conducted using Praat through the Listening Experiments feature using MFC (Multiple Forced Choice) to distinguish ten pairs of Japanese vocabulary that have the same sound but have different accent patterns. The results showed that the correct answers from the test results of students' perception of Japanese accents were 55.23%. This shows that students' ability to identify Japanese accents is in the poor category. In other words, students have not been able to distinguish Japanese accents, especially in two vocabularies that have the same sound. This is due to the influence of the accent of vocabulary that has been learned first and the lack of sensitivity of students to changes in the rise and fall of accent tones.